Clinico-epidemiological profile of nutritional anaemia and its impact on developmental outcome in children aged 6 months to 5 years - Jaiswal, Neha; Kalra, Naman; Chaudhary, Sanjata R.; Mohan, Nitesh (International Journal of Contemporary Pediatrics, 2018)
Background: Anemia is a global public health problem and is a significant contributor to the global health disease. Young children are more vulnerable to the effects of anemia since it retards the physical and mental growth and development. Objective of this study was clinico-epidemiological profile of nutritional anemia and its impact on developmental outcome in children aged 6 months to 5 years. Methods: The study was a prospective observational study. A total of 100 patients with hemoglobin <11g/dl admitted in our hospital were included in the study. Detailed clinical history with developmental assessment was elicited and thorough clinical examination was performed. Complete haemogram with Peripheral smears of these patients were examined. Bone marrow examination was done where ever possible. Results: Maximum numbers of the patients were in the range of 3 to 4 year. Proportions of anemia in males were 68% when compared to females (32%). Iron deficiency anemia (IDA) was the most common in males. The correlation between anemia and developmental delay was 7.9% in iron deficiency anemia and 87.5% in megaloblastic anemia (MBA) which was highly significantt. Conclusions: Anemia poses a biggest challenge in the improvement of primary health care particularly in young children since it is associated with delay in psychomotor development and increased morbidity and mortality. Initial screening and subsequent diagnostic tests enable early diagnosis and appropriate management.